The PMI guide to business analysis (Project Management Institute, Inc., 2017)
The PMI Guide to Business Analysis is a new PMI foundational standard, developed as a basis for business analysis for portfolio, program, and project management. This standard illustrates how project management processes and business analysis processes are complementary activities, where the primary focus of project management processes is the project and the primary focus of business analysis processes is the product. This is a process-based standard, aligned with A Guide to the Project Management Body of Knowledge (PMBOK® Guide) - Sixth Edition, and to be used as a standard framework contrib.